Patient satisfaction and wait times following outpatient manual vacuum aspiration compared to electric vacuum aspiration in the operating room: a cross-sectional study - Laura E. Dodge; Lisa G. Hofler; Michele R. Hacker; Sadia Haider (BMC, 2017)
Abstract Background Outpatient manual vacuum aspiration (MVA) is a safe and equally effective alternative to electric vacuum aspiration (EVA) in the operating room. This project was conducted to determine whether outpatient MVA expedites care while maintaining patient satisfaction. Methods A cross-sectional study of a convenience sample of patients undergoing surgical management of spontaneous abortion, induced abortion, or retained products of conception with either outpatient MVA under local anesthesia or EVA in the operating room was conducted. Of 138 women completing surveys, 48 (34.8%) underwent outpatient MVA and 90 (65.2%) underwent EVA in the operating room. Procedure length, time from decision to procedure, and patient satisfaction were assessed through a self-administered questionnaire completed post-procedure. Results Most (77%) patients in the MVA group reported waiting fewer than 2 h from the time of their decision to the procedure, while most (74%) EVA patients reported waiting over 12 h (P < 0.001); the MVA group reported higher satisfaction with time to procedure (P = 0.02). The median procedure length was significantly shorter in the EVA group (10 vs. 20 min, P < 0.001). There was no significant difference between groups in overall satisfaction with the procedure (P = 0.16). Conclusion Outpatient MVA under local anesthesia is a suitable alternative to operating room-based EVA for management of spontaneous abortion, induced abortion, and retained products of conception. Outpatient MVA is associated with shorter decision-to-procedure time and is highly acceptable to patients. Integration of outpatient MVA into clinical settings can add time- and resource-saving options for uterine evacuation while maintaining a positive patient experience.